Empowering Mustahiq Through Productive Zakat: A Maqashid Sharia Analysis of The "Surabaya Berdaya" Program - Ahmad Muqorobin; Ussholihah, Maritza (Invest Journal of Sharia & Economic Law, 2025)
This study evaluates the "Surabaya Berdaya" program initiated by BAZNAS Surabaya as a model of productive zakat aimed at empowering mustahiq through sustainable economic development. Grounded in the Maqashid Shariah framework, particularly the objective of Hifz al-Mal(protection of wealth), this study investigates the effectiveness of the program in transforming zakat beneficiaries into independent economic actors. A qualitative descriptive approach was employed, with data collected through interviews with program implementers and mustahiq, direct observations, and documentation analyses. The interview data were further analyzed using open coding techniques, allowing the emergence of key themes that were subsequently mapped to empowerment indicators. Verbatim quotations selected from informants were included to enhance methodological rigor and authenticity. The programme offers business capital, vocational training, business equipment, and ongoing mentoring to support micro-entrepreneurship. Field findings indicated increased income levels, improved financial literacy, and enhanced self-confidence among participants. Empowerment was observed through multidimensional indicators, such as self-agency, skill acquisition, resilience, and cooperative networks. The analysis shows that zakat utilization in this program aligns effectively with Maqashid Shariah, when combined with ethical governance, contextual sensitivity, and post-disbursement support. However, disparities in outcomes highlight the need for adaptive mentoring and personalized empowerment pathways. This study contributes to the growing literature on Islamic social finance by offering empirical insights into the operationalization of Maqashid Shariah in urban zakat programmes. It recommends further research into the long-term impact, integration with digital zakat systems, and policy innovation to enhance program scalability and effectiveness.